Comparison of lecturers' epistemological beliefs in teaching electromagnetic theory - Bakar, M. S. (2020)
This research was conducted to compare the epistemological beliefs of two lecturers in teaching Electromagnetic Theory course. The two lecturers were selected based on their experiences in teaching the course at a University in Malaysia. A series of interviews were conducted, audio recorded and transcribed. The data were analysed using thematic analysis approach. The research found that based on the Yu and Strobel framework of the epistemological beliefs, only a few items within the constructs were undefined and most of the items meet the learning environments.